ANALYSIS OF STUDENTS' MATHEMATICAL PROBLEM-SOLVING ABILITIES IN REVIEW OF INTROVERT AND EXTROVERT PERSONALITY TYPES - Andi Ilham Akbar Hasanuddin (Universitas Sebelas Maret, 2024)
The objective of this research is to delineate the mathematical problem-solving skills of students based on their introverted and extroverted personality types. The research methodology employed is descriptive research, utilizing a qualitative approach. The subject selection technique used was purposive sampling, which was as many as 4 students, specifically, the study involves 2 students with introverted personality types and 2 with extroverted personality types. Data analysis involves techniques such as data condensation, data presentation, and conclusion/verification. The findings indicated that (1) Class XI students of SMAN 5 Wajo with introverted personality types have high mathematical problem solvingskills where students are able to meet all indicators, namely: a) the stage of understanding the problem, b) the stage of devising a plan, c) the stage of carry out the plan; and d) able to looking back. (2) Grade XI students of SMAN 5 Wajo with extroverted personality type have low mathematical problem-solving skills where students are able to meet two indicators, namely: a) the stage of understanding the problem, b) the stage of devising a plan, c) unable to carry out the plan; and d) unable to looking back.